1997
DOI: 10.1076/ceyr.16.10.1036.9015
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathologic features of Staphylococcus epidermidis-induced endophthalmitis in the rat

Abstract: The vitreous antibodies may be involved in neutrophil-mediated opsonophagocytosis leading to 'spontaneous sterility' of the bacteria, and may play a role in the immunopathogenesis of staphylococcal endophthalmitis in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…In contrast with the unfavorable natural history of untreated infectious endophthalmitis seen invariably in humans, spontaneous regression of S. epidermidis endophthalmitis has been described in the rat, showing its capacity to beat the infection without treatment [23]. Rabbits have shown a similar capacity in eradicating bacteria [14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast with the unfavorable natural history of untreated infectious endophthalmitis seen invariably in humans, spontaneous regression of S. epidermidis endophthalmitis has been described in the rat, showing its capacity to beat the infection without treatment [23]. Rabbits have shown a similar capacity in eradicating bacteria [14].…”
Section: Discussionmentioning
confidence: 96%
“…Staphylococcus epidermidis slime-positive ATCC strain 35983 was used to infect the experimental group as follows. Each one of the 72 experimental rats received a 50-μl intravitreal pars plana injection of approximately 7000 viable organisms in the right eye according to a previously described model [23], while a similar sterile normal saline injection was given to each one of the 72 control rats in the right eye (placebo group). Each eye had been dilated with sterile 1% atropine eye drops so as to watch needle placement and to prevent nicking of the lens.…”
Section: Animals-bacterial Strain-intravitreal Injectionsmentioning
confidence: 99%
“…Previous animal research has shown that inflammation appears soon, peaking at day 1 post-inoculation [15,18]. Neutrophils in the vitreous peak also at day 1 and decrease by day 7, whereas plasma cells increase between days 1 and 3 postinoculation [20]. Proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin-1-beta (IL-1β), and interferon-gamma (IFN-γ), are expressed in the vitreous, and this expression is closely related to clinical inflammatory scores [18].…”
Section: Introductionmentioning
confidence: 91%
“…The slime-producing S. epidermidis strain ATCC 35983 was used to infect the experimental group as follows: Each one of the 48 experimental rats received a 25-μl intravitreal pars plana injection of approximately 7,000 viable colonyforming units (CFU) in the right eye, according to a previously established model [20]. Moreover, 25 μl of the same S. epidermidis suspension were plated on blood agar and incubated at 37°C; colony counts at 48 hours confirmed the actual number of S. epidermidis CFU injected.…”
Section: Induction Of Endophthalmitismentioning
confidence: 99%
“…For this reason, another animal model was needed to further characterize the immunologic mechanisms associated with bacterial endophthalmitis. Ravindranath et al [103, 104]developed a rat model of both S. epidermidis and S. aureus endophthalmitis to examine the immunologic responses to staphylococci. In these studies, Lewis rats received intravitreal injections of viable S. aureus or S. epidermidis .…”
Section: Immune Response Studiesmentioning
confidence: 99%